Preliminary osteogenic and antibacterial investigations of wood derived antibiotic-loaded bone substitute for the treatment of infected bone defects - Salamanna, Francesca; De Luca, Angela; Vandenbulcke, Filippo; Di Matteo, Berardo; Kon, Elizaveta; Grassi, Alberto; Ballardini, Alberto; Morozzi, Giacomo; Raimondi, Lavinia; Bellavia, Daniele; Costa, Viviana; Zaffagnini, Stefano; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: The development of reliable treatments for infected or potentially infected bone loss resulting from open fractures and non-unions is extremely urgent, especially to reduce the prolonged courses of antimicrobial therapy to which affected patients are subjected. Numerous bone graft substitutes have been used over the years, but there are currently no effective solutions to treat critical bone loss, especially in the presence of infection. The present study evaluated the use of the biomorphic calcium phosphate bone scaffold b. Bone™, based on a next-generation resorbable biomimetic biomaterial, in bone reconstruction surgery in cases of infection. Methods: Using an “in vitro 3D bone fracture model” to predict the behavior of this drug delivery system during critical bone loss at an infected (or potentially infected) site, the effects of scaffolds loaded with gentamicin or vancomycin on the viability and differentiation capacity of human mesenchymal stem cells (hMSCs) were evaluated. Results: This scaffold, when loaded with gentamicin or vancomycin, exhibits a typical drug release curve that determines the inhibitory effects on the growth of Staphylococcus aureus, Enterococcus faecalis, and Escherichia coli, as well as relative biofilm formation. Discussion: The study demonstrates that b.bone scaffolds can effectively address key challenges in orthopedic surgery and patient care by inhibiting bacterial growth and biofilm formation through rapid, potent antibiotic release, reducing the risk of treatment failure due to resistance, and providing a promising solution for bone infections and improved patient outcomes. Future studies could explore the combination of different antibiotics on these scaffolds for more tailored and effective treatments against post-traumatic osteomyelitis pathogens.